Twenty-five-year-old Woman with Bilateral Borderline Ovarian Tumour Desiring to Preserve Fertility – Case Report and Literature Review on the Current State of Fertility Preservation in Women with Borderline Ovarian Tumours - Findeklee, S.; Lotz, L.; Heusinger, K.; Hoffmann, I.; Dittrich, R.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2016)
Borderline ovarian tumours are semimalignant tumours occurring unilaterally or bilaterally with a peak incidence among women of reproductive age. Since the affected women often wish to preserve fertility, particular precautions must be taken when counselling the patient and obtaining consent prior to planning an individual treatment. Options for preserving fertility include an organ-sparing surgical procedure and cryopreservation of oocytes and/or ovarian tissue. In this article, we report on a 25-year-old patient with a bilateral seromucinous borderline tumour who desired all fertility-preserving options. In order to perform the procedure without delay, we opted to perform luteal phase stimulation prior to oocyte retrieval. We conclude by discussing the current literature on the state of fertility preservation in the treatment of borderline ovarian tumours.
Keywords: borderline tumour; fertility preservation; future wish for child; luteal phase stimulation; ovarian cryopreservation